Development of a Measure of Perceived Work Environment (PWE) - Newman, John E. (Academy of Management Journal, 1977)
The purpose of this research program was to develop a comprehensive and reliable measure of employee perceptions of the work environment (PWE). The PWE measure is designed to aid researchers and practitioners in assessing the current state of a given work environment and in evaluating the effect of programs aimed at modifying organized work environments. The PWE scales provide measures of 11 empirically-derived dimensions of perceived work environment. Reliability, validity, and stability data based on five data collections involving 1,200 employees in four organizations indicate that the PWE measure has quite satisfactory psychometric characteristics.